LEGALITY AND CONTROVERSY: THE DEATH PENALTY IN INDONESIA FROM THE PERSPECTIVES OF ISLAMIC LAW, CRIMINAL LAW AND HUMAN RIGHTS - Mohas, Muhyi; Rofiana, Reine; Jastisia, Mentari; Anwar, Jarkasi; Risyawan, Alief (Tirtayasa Journal of International Law, 2025)
The legality of the death penalty remains controversial as it often conflicts with the right to life. Therefore, this study was aimed to examine the legality of imposing death penalty from the perspectives of Criminal Law, Islamic Law, and Human Rights. This research used normative legal research and empirical research methods. The result showed that The death penalty in Aceh is known as "hukum pancung" (beheading) In Islam, there is also a criminal law known as qishash. The meaning of qishash is apple-to-apple retribution. This serves as the foundational rationale for Aceh's legalization of the death penalty, grounded in its implementation of Islamic Sharia and its unique legal autonomy within Indonesia. The death penalty is firmly regulated in Article 10 of the Indonesian Criminal Code (KUHP), Article 100 of the Indonesian Criminal Code Number 1 of 2023 and other Indonesian regulations inline with the death penalty. the death penalty philosophically aims to prioritize the greater good, preventing others from committing similar crimes, and alleviating societal unrest caused by rampant criminal cases. In the perspective of human rights, the application of the death penalty encompasses two theories: Universalism and Cultural Relativism. Indonesia adopts the principle of cultural relativism. the death penalty can be imposed by authorized law enforcement officers, provided that the case or act falls within the category of severe crimes and violations. This Research gives contribution related the reasons and all considerations underlying the regulation of the death penalty according to Islamic law, criminal law and human rights.